2D Boron Nitride Nanosheets for Smart Thermal Management and Advanced Dielectrics. Issue 25 (4th August 2022) - Wu, Min; Zhou, Yuanliang; Zhang, Han; Liao, Wugang
Abstract: With the rapid development of electronic devices toward the miniaturization, integration, and multi‐functionalization, the device stability, reliability, and service life face significant challenges due to the greatly increased heat accumulation. Therefore, it is highly desired to develop efficient thermal dissipation materials in thermal management. Thermally conductive polymer composites are expected to be widely applied in 5G communication, electronic packaging, and energy storage, owing to the ease of processing, good flexibility, low cost, etc. Boron nitride nanosheet (BNNS) is generally used as highly thermal conductive nanofillers for greatly improving the thermal conductivity of polymer. Mass production of high quality BNNS with desired properties and the structural design principles and fabrication methods for polymer/BNNS nanocomposites are critical to achieve extensive applications. Here, this review summarizes the latest advancement of the preparation method of BNNS and its polymer nanocomposites, as well as the innovatively structural design for observably improving the thermal management capability and energy storage performance of polymer/BNNS nanocomposites, expecting to offer some guidance on how to massively fabricate the BNNS and highly thermally conductive polymer composites. Abstract : This review paper summarizes the latest advances of the preparation method of Boron nitride nanosheet (BNNS) and its polymer nanocomposites, as well as the innovatively structural design for observably improving the thermal management capability and energy storage performance of polymer/BNNS nanocomposites.